Is engagement different from satisfaction and organizational commitment? Relations with intention to remain, psychological well-being and perceived physical health in volunteers - Vecina, María Luisa; Chacón, Fernando (Anales de Psicología / Annals of Psychology, 2013)
In a sample of volunteers, who work, but not for money, and whose managers expect them to remain with the organization over the long term and to feel well by doing good, this study examines the distinctiveness between three concepts, usually related in the work field: Engagement, organizational commitment, and satisfaction. Based on the existing literature, they are related among them and regarding three relevant outcomes for management: Intention to remain, psychological well-being, and perceived physical health. Three structural equations models make it clear that volunteer engagement does contribute to the explanation of organizational commitment, volunteer satisfaction, and psychological well-being. At the same time, it does not seem to account for levels of intention to remain neither perceived physical health. On the contrary, organizational commitment is the only predictor of intention to remain, and volunteer satisfaction is the only predictor of perceived physical health. This last result was not expected, according to the literature on work, but reinforces the distinctiveness between the concepts and may have a plausible explanation in the volunteering field.